Human Health Risk Assessment Data of Selected Trace Elements' Concentrations in Floodplain Water of Jebba-North, Central Nigeria - Omotoso, Oladele Ajiboro; Ojo, Olusola Johnson; Ige, Olusegun Omoniyi; Cole, Oluwadamilare; Okunnoye, Olumide; Ariba, Adebola Oreoluwa; Olelewe, Michael Chukwudi (Journal of Science and Technology, 2020)
The consumption of the water from the floodplain of River-Niger by denizens of Jebba-North pose a significant health risk, as it is being exposed to waste from industries, agricultural facilities and households from the congested urban areas. The risk is more pronounced as people living near floodplain uses it for their domestic needs. The study uses ICP-MS method to analyse water from the samples' area; and the exploratory analyses of the water for the following trace elements: "Al, As, Ba, Cd, Cr, Cu, Fe, Mn, Ni, Pb, and Zn" were carried out. The analyses showed that the mean daily intake by both adult and children, using the Hazard Index (HI) and Hazard Quotient (HQ) of the elements, except Cr and Pb was >1; this is above the standard prescription of